Mathematical modeling of the electric spark ignition of the coal-water particle fuel under conditions relevant to the internal combustion engines; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Syrodoy S. V. Semen Vladimirovich; Penyazkov O. Oleg; Assad M. Mohamad; Gutareva N. Yu. Nadezhda Yurievna (2017, 2017)
Title screen